PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS ANDROID PADA TOPIK PERSAMAAN KUADRAT BAGI PESERTA DIDIK KELAS XI SMK - Anisa Yanti Efendi (Departemen Matematika, 2022)
This study aims to develop android-based interactive multimedia in mathematics subjects at SMKN 2 Padang which can be used to facilitate educators and students in the learning process. The media, which was developed with the help of smart apps creator software, is to determine the validity and practicality of products that combine several formats such as text, images, animation, video, and audio. This research is a development research (Research and Development) with the Plomp development model with stages, namely: initial investigation stage, development stage, and assessment stage, but in this study only two stages were carried out. The instruments in this research are validity and practicality questionnaires. The developed media was tested on three students in the One-to-one Evaluation and six students in the Small Group Evaluation with different cognitive abilities. Based on the results of the analysis of the validity data, it shows the level of validity with the percentage (1) Material expert assessment reaches 83.33% with a very valid category, (2) Media expert assessment reaches 83.157% with a very valid category, (3) Linguistics expert assessment, namely SMKN 2 Educators Padang reached 97.89% with a very valid category, and (4) Expert assessment reached 84.21% with a very valid category. Interactive multimedia also meets the practical criteria from the questionnaire responses of three students who have carried out One-to-One Evaluation with a percentage of 84.44%. While the results of the student response questionnaire on the Small Group Evaluation with a percentage of 92.22% the criteria are very practical. Keywords – Research development, android, interactive multimedia, Smart Apps Creator